The Role of Accountability towards FDI Attractiveness Evidence from Malaysia (International Journal of Psychosocial Rehabilitation, 2020)
The ability of any country to attract FDI inflows is considered to depend on the quality of the economic accountability found within that country. Accountability reflects perceptions of the extent to which a country's citizens are able to participate in selecting their government, as well as freedom of expression, freedom of association, and a free media. This study conducts empirical analysis and focuses on some FDI determinant variables such as accountability performance, GDP, and poverty level. Data of observation from the years 2008 to 2018 is extracted from the World Bank database to find out the relationship of the variables. In this study, a yearly time series panel data from the period of 2008 to 2018 estimates from Malaysia were used. This study finds evidence that countries with strong legal systems are remunerated with higher levels of FDI inflows. For the random and fixed effects method, the value of the coefficient determined the positive or negative relationship between those variables and the accountability and FDI inflows. The stationary properties of the time series were performed in accordance with the unit root test. The results extracted from the unit root test indicated that under intercept and intercept with trend for FDI inflows, all variables at level seem to be stationary at a significance of 1%. The same result appears under intercept with trend. Lastly, accountability has a significant influence on FDI inflows in Malaysia. This indicates that foreign investors are interested in political stability and regulatory quality in their choice of investment abroad. The government is responsible for ensuring that the new policy is assigned accountability with FDI inflows by the relevant policies.